Factors Affecting Gut Microbiota of Puppies from Birth to Weaning - Fatemeh Balouei; Bruno Stefanon; Sandy Sgorlon; Misa Sandri (Animals, 2023)
The review described the most important factors affecting the development of the intestinal microbiota in puppies from birth to weaning. The health and well-being of the microbiome in puppies is influenced by the type of parturition, the maternal microbiota, and the diet of the mother, directly or indirectly. The isolation of bacteria in dogs from the placenta, fetal fluids, and fetuses suggests that colonization could occur before birth, although this is still a matter of debate. Accordingly, newborn puppies could harbor bacteria that could be of maternal origin and that could influence microbial colonization later in life. However, the long-term impacts on health and the clinical significance of this transfer is not yet clear and needs to be investigated. The same maternal bacteria were found in puppies that were born vaginally and in those delivered via cesarean section. Potentially, the relationship between the type of parturition and the colonization of the microbiome will influence the occurrence of diseases, since it can modulate the gut microbiome during early life. In addition, puppies’ gut microbiota becomes progressively more similar to adult dogs at weaning, as a consequence of the transition from milk to solid food that works together with behavioral factors. A number of researches have investigated the effects of diet on the gut microbiota of dogs, revealing that dietary interference may affect the microbial composition and activity through the production of short-chain fatty acids and vitamins. These compounds play a fundamental role during the development of the fetus and the initial growth of the puppy. The composition of the diet fed during pregnancy to the bitches is also an important factor to consider for the health of newborns. As far as it is known, the effects of the type of parturition, the maternal microbiota, and the diet on the microbial colonization and the long-term health of the dogs deserve further studies. Definitely, longitudinal studies with a larger number of dogs will be required to assess a causal link between microbiome composition in puppies and diseases in adult dogs.